The Impact of Concentration Toward Soccer Player Shooting Ability of Soccer School Batuang Taba Padang City - Tjung Hauw Sin; Marjan Aprinanda (International Journal of Research in Counseling and Education, 2020)
The problem of this research was soccer player shooting ability of Soccer School Batuang Taba still low. It can be seen from the decreasing of their achievement that happened in Soccer School Batuang Taba. The aim of this study is to reveal the direct impact of Concentration, on Shooting ability of soccer player. This research method is quantitive by using Path Analysis approach. Population are 19 soccer players of U-15 Soccer School Batuang Taba. The sample technique is done by Proportionate Random Sampling, so the participants became 17 soccer players. The instrument was shooting ability test. Grid Concentration, exercise for measuring Concentration. Technique of data analysis used with Path Analysis. The result of research and data analysis showed that: Concentration has a direct and significant effect on Shooting ability of 12.25%.